Dance Tourism Business Models in Seville and Buenos Aires: dimensions of meaning of intangible cultural assets in destination management - Tatjana Thimm (Via@)
Flamenco and tango are among the first associations which come to mind in connection with Seville and Buenos Aires. Ever since both art forms appeared in the 19th century, a form of dance tourism has been constantly evolving, giving rise to differentiated business models right up to the present day. Moreover, as intangible world cultural assets, flamenco and tango have acquired considerable importance for the destination image of both cities. The ‘governance of global value chains’ model of Gereffi et al. (2005) is here applied in adapted form to flamenco and tango dance tourism in order to derive dimensions of meaning in destination management.